2020
DOI: 10.7150/thno.46878
|View full text |Cite
|
Sign up to set email alerts
|

A feedforward circuit shaped by ECT2 and USP7 contributes to breast carcinogenesis

Abstract: Rationale: A number of guanine nucleotide exchange factors (GEFs) including epithelial cell transforming factor ECT2 are believed to drive carcinogenesis through activating distinct oncogenic GTPases. Yet, whether GEF-independent activity of ECT2 also plays a role in tumorigenesis remains unclear. Methods: Immunohistochemical (IHC) staining, colony formation and xenograft assays were used to examine the role of ECT2 in breast carcinogenesis. Co-immunoprecipitation, immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 87 publications
(131 reference statements)
0
13
0
Order By: Relevance
“…As reported by ourselves and others, ECT2 is a potential oncogene that promotes breast tumorigenesis ( 35 , 40 , 41 , 42 , 43 ). Therefore, we wondered if the high expression level of ECT2 found in breast cancer confers cellular resistance to genotoxic insults.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…As reported by ourselves and others, ECT2 is a potential oncogene that promotes breast tumorigenesis ( 35 , 40 , 41 , 42 , 43 ). Therefore, we wondered if the high expression level of ECT2 found in breast cancer confers cellular resistance to genotoxic insults.…”
Section: Resultsmentioning
confidence: 61%
“…Increasing evidence, including our previous study, indicates that dysregulated ECT2 activity is implicated in many types of cancer and that ECT2 depletion suppresses tumorigenesis ( 35 , 41 , 52 , 53 ). These findings suggest that ECT2 acts as an oncogenic protein.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Recent studies showed the effects of FTO 77 , protein arginine methyltransferase 1 (PRMT1) 78 , coactivator associated arginine methyltransferase 1 (CARM1)/PRMT4 79 , Otubain-2 (OTUB2) 80 , RING finger protein 144A (RNF144A) 81 , plant homeodomain finger protein 20-like protein 1 (PHF20L1) 82 , heat shock transcription factor 1 (HSF1) 83 , epithelial cell transforming sequence 2 (ECT2) 84 , pescadillo homolog 1 (PES1) 85 , PHACTR2-AS1 (PAS1) 86 , breast cancer-related transcript 1 (BCRT1) 87 , and circCDYL 88 on progression of breast cancer and they provided novel therapeutic targets. TNBC is especially hard to treat due to the lack of targets.…”
Section: Novel Therapeutic Targets and New Drugsmentioning
confidence: 99%
“…Importantly, USP7 is able to interact with itself and remove its own polyubiquitin chains to sustain self-stability. In addition, this process is observed to be promoted by ECT2, indicating USP7 and ECT2 also construct a positive feedback loop similar to the USP7–PHF8 loop [ 32 ].…”
Section: Dubs In Breast Cancer Growthmentioning
confidence: 99%